Assessment of ultra-lean burn characteristics for a stratified-charge direct-injection spark-ignition methanol engine under different high compression ratios. (1st March 2020) - Gong, Changming; Yi, Lin; Zhang, Zilei; Sun, Jingzhen; Liu, Fenghua
Highlights: Ultra-lean burn characteristics of spark ignition methanol engine was assessed. A non-uniform spray-line nozzle was adopted to achieve stratified mixture. Equivalence ratio of methanol engine at high compression ratio is as low as 0.20. Thermal efficiency increases with decrease high compression ratio at ultra-lean burn. Abstract: Lean burn is one of the most important characteristics of a stratified-charge direct-injection spark-ignition engine. In this study, a non-uniform 10-hole × 0.30 mm spray-line distribution nozzle was chosen to achieve stratified-charge of the methanol/air mixture. The mixture formation, combustion, and emissions characteristics of a stratified-charge direct-injection spark-ignition methanol engine under five global equivalence ratios and three high-compression ratios were simulated to assess its ultra-lean burn characteristics. The results showed that the equivalence ratio of the stratified-charge direct-injection spark-ignition methanol engine for stable combustion at high compression ratio was as low as 0.20. The ignition delay and combustion duration decreased as the compression ratio increased at high equivalence ratio, and vice versa at low equivalence ratio. The stratified-charge direct-injection spark-ignition methanol engine greatly reduced nitric oxide emissions under ultra-lean combustion. The unburned methanol, carbon monoxide, and soot emissions increased slowly as equivalence ratio decreased at all compression ratios and equivalence ratio >0.25. The indicated thermal efficiency decreased with decreasing compression ratio at high equivalence ratio, and vice versa at low equivalence ratio. For an equivalence ratio of 0.67, the indicated thermal efficiency at compression ratio of 14 was approximately 14.9% lower than at compression ratio of 16. However, for an equivalence ratio of 0.20, the indicated thermal efficiency at compression ratio of 14 was approximately 13.5% higher than at compression ratio of 16. The compression ratio of 14 was more favorable for the stratified-charge direct-injection spark-ignition methanol engine to achieve ultra-lean burn and find practical application.